Manuscript Writing Guidelines: Analysis of Creative thinking skills profile of Senior High school students in Madiun City on Biotechnology topic - Nurdiana, Herning; Nurcahyo, Ima Agung; Primiani, Cicilia Novi (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Currently, the world of education has returned to normal after the outbreak of Covid-19. The newest curriculum implemented in Indonesia is the independent curriculum. One of the important competencies trained in the independence curriculum is creative thinking skills. Creative thinking skills are important for long-term success because they help see problems and situations from different perspectives to solve problems. The purpose of this study was to analyze the profile of students' creative thinking skills in biotechnology material. This research is a descriptive research with a written test method that includes creative thinking skills. The subjects of this study were 35 students of SMAN 6 Madiun who were selected using a purposive sampling technique. The results obtained show that the percentage of achievement of creative thinking skills as measured using 4 aspects of adaptive creative thinking skills according to Torrance and Guildford namely fluency 60%, flexibility 44,64%, originality 40,36%, and elaboration 57,85%.